Cormorant pellets as a tool for the knowledge of parasite-intermediate host associations and nematode diversity in the environment - Garbin, Lucas; Diaz, Julia Inés; Morgenthaler, Annick; Millones, Ana; Kuba, Luisa; Fuchs, Daniela Viviana; Navone, Graciela Teresa (Helminthologia)
Anisakids are usually acquired through the diet. Cormorant pellets are useful to detect both parasite larval stages, and prey items which could act as intermediate hosts in the environment. The current study provides information about the feeding habits of both birds and mammals, and the diversity of parasites circulating in the environment. The objective of the study was to identify Anisakidae larvae and prey items in pellets from the Imperial shag Phalacrocorax atriceps and the Red-legged cormorant P. gaimardi, suggesting possible parasite-prey associations. A total of 92 P. atriceps' and 82 P. gaimardi's pellets were collected from both Punta León, and Isla Elena bird colonies, respectively, during the period from 2006 to 2010. Pellets were preserved in ethanol and hard prey item remnants, and nematode larvae were studied using standard techniques. Prey item occurrence, nematode prevalence, and mean intensity were calculated. A correspondence analysis was performed to evaluate the larvae-prey association. Contracaecum spp., Pseudoterranova spp, Anisakis spp., Terranova spp., and Hysterothylacium spp. third-stage larvae (L3) were identifi ed in pellets. Pseudoterranova spp. and Anisakis spp. L3 predominated in the environment of Punta León, whereas Contracaecum spp. and Hysterothylacium spp. L3 predominated in the Puerto Deseado area. The highest larvae-prey association was that of Contracaecum spp. L3 with Engraulis anchoita, followed by with Odontestes sp. in P. atriceps' pellets. Contracaecum spp. L3 were significantly related to both sprats, Sprattus fueguensis and Ramnogaster arcuatta, in P. gaimardi's pellets. It was verifi ed that E. anchovy is the main gateway of Contracaecum spp. L3 in P. atriceps. Odonthestes sp. might act as an intermediate/paratenic host of Contracaecum spp. L3 in the area. Both sprats might play a role as intermediate/paratenic hosts of C. australe, being the main gateway into P. gaimardi in the area. Thus, pellet analysis can be postulated as a good tool for indicating ...